Ballistic impact on composite armour - Bourke, Paul (Cranfield University, 2007)
Armoured vehicles in current military service are requiring ever more protection to enable them to carry out their mission in a safe, effective manner. This requirement is driving vehicle weight up to such an extent that the logistics of vehicle transport is becoming increasingly difficult. Composite materials are an important material group whose high specific properties can enable structures to be manufactured for a far lower weight than might otherwise be possible. Composite materials in an armoured vehicle will require structural performance as well as ballistic performance. The mechanical and ballistic performance of tl-kk armour and structural composites has been investigated against dcformable and armour-piercing ammunitions, over a range of impact velocities. Testing has indicated that heavy/coarse reinforcement weaves perform well against deformable ammunition and light/fine weaves well against armour piercing ammunition. The effect of individual mechanical properties on ballistic performance has been investigated as has the damage morphology of impacted materials. High tensile strength combined with low fracture toughness has been identified as an important requirement. Failure mechanisms have been identified from sections of ballistic impacts and through the use of mechanical test data the energy absorbed by each mechanism has been calculated. An energy audit has been carried out of all materials tested and a modelling procedure developed based on mechanical characteristics, damage morphology and failure mechanisms. This model has been tested against literature results and found to give very satisfactory performance.
Keywords: Firearms; Terminal ballistics; Explosion effects; Armoured fighting vehicles; Ballistic performance; Composite armour